Production of novel aluminium by additive manufacturing - Ayarkwa, Kwasi Frimpong (Cranfield University, 2018)
Aluminium matrix composites are required by manufacturers to produce light weight components or parts with improved mechanical properties over conventional aluminium alloys. These materials are useful for complex structures with locally strengthened properties which are difficult to produce by conventional techniques such as subtractive and formative processes. In this research wire and powder feed additive manufacture processes were investigated for their suitability for producing aluminium matrix particle reinforced composites as an alternative to conventional processes. The research focusses on the use of wire + powder additive manufacture to produce aluminium silicon carbide composites. Different process variants were investigated including the use of either gas metal arc, gas tungsten arc or a laser as the heat source. In depth investigations of the main process parameters such as travel speed, arc or laser power were carried out. Of these both the gas tungsten arc and the laser proved to be viable options. It was found that a melt pool with as high a temperature as possible is required to successfully inject particles into the melt. Therefore it was found necessary to insulate the substrate in which the melt bead was being generated. Detailed studies into the other controlling factors for embedding the SiC particles into aluminium melt pool were explored. It was found that the most important are the nozzle feeding direction, particle size, particle velocity and type of shielding gas. For example, it was necessary to use 150 μm SiC particles in order to successfully break the surface oxides and penetrate the melt pool correspondingly. For the arc based processes using helium as the shielding gas was highly beneficial as it resulted in a much larger melt pool size in comparison to using argon. It was found that particles were distributed at the top and bottom surface of helium produced melt beads. On the other hand, particles were mainly distributed at the top surface of argon and laser melt injected melt beads. For the laser process, the particles penetrated more than 1.5 mm into the melt bead. Finally the investigation showed that increasing the particle feed rate and heat input increases the % volume fraction of SiC reinforcement particles captured.
PhD in Manufacturing
Keywords: Wire + arc additive manufacture; metal matrix composites; silicon carbide; tungsten inert gas; cold metal transfer